Identification of Senior High School Students' Problem-Solving Skill on Static Electricity Based on Gender - Nurul Atqiya; Dibyaratna Sy.; M. Pathurrozi; Sentot Kusairi (Berkala Ilmiah Pendidikan Fisika, 2021)
This research aimed to identify differences in problem solving skill between male and female students. The research subjects were 50 students (21 male and 29 female) who were taken by random sampling technique from two high schools in Malang. The research instrument was adapted from problem solving instruments of Maries & Singh (2018). The data was analyzed by statistic descriptive and Kruskall Wallis test (p-value <0.05). The results showed that overall, there was no significant difference between male and female students (p-value>0.05). However male students performed better than female students on preparing the action (p-value<0.05). The results of this research can be a consideration and input for practitioners of education to improve the quality of education, especially in Indonesia.